Gastric carcinoid tumor resected with endoscopic polypectomy - Selim GÜREL; Enver DOLAR; Selim Giray NAK; Gülaydan FİLİZ; Macit GÜLTEN; Yusuf KARAASLAN; Ömer YERCİ; Faruk MEMİK (Turkish Journal of Gastroenterology, 2019)
-